The Routledge handbook of disability sport science / edited by Katy Griggs, Ursina Arnet, Rienk van der Slikke and Joelle Leonie Flueck. - Griggs, Katy; Arnet, Ursina; Slikke, Rienk van der; Flueck, Joelle Leonie (Routledge international handbooks., 2026)
'The Routledge Handbook of Disability Sport Science' offers a comprehensive and in-depth review of current and emerging topics within disability sport science and provides a complete overview of academic and professional knowledge, divided into six sections.